Attaining and assessing the Australian interprofessional learning competencies. - Gordon, Susan; Lind, Christopher; Hall, Karinna; Baker, Nicky (Journal of Interprofessional Care)
Interprofessional collaboration is critical for optimal healthcare. Preparing for a collaborative, practice-ready workforce, the Interprofessional Learning Competencies (IPLCs) were adopted for accreditation of Australian entry-level health, nursing and medical tertiary training programs. In order to meet new accreditation standards, activities which facilitate and assess IPLC attainment must be identified. Interprofessional education programs have not evaluated student interprofessional learning activities using the Australian IPLCs. This project evaluates students' experiences of the IPLCs during 'Inspiring Health,' a community-based interprofessional placement, and determines whether reflections can effectively assess IPLC attainment. Forty-nine students from seven Flinders University health and social science programs completed written reflections about four self-selected IPLCs. The results indicated that students had opportunities to attain all the IPLCs. Their reflections were analyzed using thematic analysis. Three themes were identified: the processes by which students learned, the outcomes of their learning, and the factors that influenced their learning. Ultimately, these findings describe a beneficial community-based interprofessional learning activity for attainment of the Australian IPLCs and provide evidence that student reflections can be used to assess the Australian IPLCs.